Effect of deposition rate on micromorphology analyses and optical parameters in amorphous carbon nickel thin films - Mostafa Khanmohammadi Padervand; Vali Dalouji; Dariush Mehrparvar (Scientific Reports)
Abstract In this work, the micromorphology of the Ni @ amorphous carbon films and their relationship to other optical properties using atomic force microscopic (AFM) imaging were examined. The surface topography of these Ni @ amorphous carbon sheets was reported using stereometric analysis and the SPIPTM 6.7.4 software in compliance with ISO 25178-2:2012 and ASME B46.1-2009. It is clear that the Ni @ amorphous carbon films deposited at 180 s had more the root mean square height (Sq) at around of 0.1475 mm and has the greatest value in comparison to other films. The Ni @ amorphous carbon films deposited at 600 s had a more regular surface because their the root mean square height (Sq) had minimum value of 0.1360 mm. The peak energy positions of optical density for the films deposited at 180 s which were the lowest value and about of 1.65 eV, could be due the quasi-metallic mode. The cut-off energy for the skin/shell depth parameters of the Ni @ amorphous carbon films were about 3.5 eV/ or 353 nm. The Ni @ amorphous carbon films deposited at 180 s had the lowest value of the electron - phonon interaction energy, (Ee-p). The small polaron model shown that as input photon energy was increased, the calculated AC conductivity by optical data for the Ni @ amorphous carbon films was decreased.